Homeostase de ferro em Paracoccidioides spp.: novos alvos de estudo e estabelecimento de HSP30 como proteína ligante de hemoglobina - Souza, Aparecido Ferreira de (2021)
Understanding the mechanisms that govern host-pathogen interaction is crucial for the development of new therapeutic and diagnostic approaches. Fungi of Paracoccidioides genus are the etiological agents of paracoccidioidomycosis, a systemic mycosis and, when in the host, fungi find a hostile environment that is scarce in nutrients and micronutrients, such as Fe, which is indispensable for the survival of the pathogen. Previous studies have shown that fungi of this genus, in response to Fe deprivation, are able to synthesize and capture siderophores (Fe3+ chelators), use host proteins that contain Fe as metal’s source and use a non-canonical reductive pathway for assimilation of Fe. Despite all these findings, there are still gaps that need to be filled regarding the pathogen's response to Fe deprivation. In the present work, targets that still need to be studied in this context were defined, such as the establishment of the protein functions of the fungus that contain the CFEM domain and the determination of the specificity of siderophore receptors. Additionally, it was shown that the exposure of Paracoccidioides to hemoglobin promotes changes at fungal cell wall proteome level, which is illustrated by the increased ability of the fungus to interact with macrophages. This approach allowed the bioprospecting of the hemoglobin-binding protein HSP30, which is present on the cell surface and has its expression regulated positively when the fungus is exposed to hemoglobin. It has been shown that silencing of hsp30 causes decreased growth of the fungus after exposure to hemoglobin. It is also necessary to investigate the function of HSP30 as heme oxygenase. The detailed observation of those open questions can promote the expansion of knowledge about the biology of Paracoccidioides spp. and, consequently, promote the bioprospecting of new targets for differential diagnosis and/or therapy of PCM.